EDUKASI PRA NIKAH DAN WORKSHOP PERLINDUNGAN PEREMPUAN DAN ANAK MEMPERSIAPKAN KELUARGA MUDA YANG BERENCANA UNTUK MENDUKUNG SDGs 03 (GOOD HEALTH AND WELL-BEING) - Ashrisnaini, Yudhia; Utami, Wiwid; Tajul Ma’arif, Muh; Wijayanto, Heri; Garnika, Eneng; Rayani, Dewi; Khairani Ardi, Komala; Febriyansyah, Benny; Widyani, Aprillian; Reyhan Adiba, Rahmat; Nabilla Maharani, Sisilia; Rian Maulidani, Ahmad; Widia Lingga, Elza; Fadlurrahman, Firgi (Jurnal Wicara, 2025)
Marriage is one of the social institutions that plays an important role in the lives of individuals and society. However, the lack of pre-marriage education often triggers various problems of unfair treatment of women and children. In Sepakek Village, Pringgarata District, Central Lombok Regency, the high phenomenon of early marriage in this area is a major concern, because it can increase the risk of divorce, domestic violence, and other negative impacts on maternal and child health. The Community Service Student Work Lecture (KKN PMD) University Of Mataram in Sepakek Village, Pringgarata District, Central Lombok Regency, aims to enhance the understanding of the youth regarding pre-marital education and the protection of women and children. In the context of Sustainable Development Goals (SDGs) number 04, which emphasizes the importance of quality education, this activity includes socialization and workshops that provide knowledge about the prevention of early marriage and the rights of women and children. The results of this activity indicate an increase in youth participation, as well as a heightened awareness of the importance of pre-marital education and the protection of women and children. It is hoped that similar activities can be held regularly to address issues of early marriage and violence against women and children in the village.